Survival of professional CS:GO teams: What matters? A research note - Timo Schöber; Georg Stadtmann; Petr Parshakov (European University Viadrina, Department of Business Administration and Economics, 2021)
We analyse Esport data of professional CS:GO teams to shed light on the question of whether diverse teams survive longer. We also control for the prize money as a time dependent covariate. Another focus is on the liability of newness hypothesis.
Keywords: 330; Diversity; survival; gaming; e-Sports; liability of newness